(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Digitalization is very important for every company in today’s fierce competition. The development of Information Technologies has helped companies change means of reaching their clients and changing their working practices. The paper tries to assess digital marketing (DM) and digital transformation (DT) techniques that impact enterprises in Kosovo in the process of their brand promotion and brand positioning using google analytics, social media, e-commerce, search engines, mobile apps, or other digital channels. DT is profoundly important to every company, yet the correlation between DT, brand promotion, and brand positioning for Kosovo’s enterprises has not been researched a lot. With the DT, many companies are redefining business procedures and marketing strategies. The research will collect data using a survey with 150 companies generated by the Kosovo Business Registration Agency. Partial Least Square is used to analyse the collected data. Structural Equation modelling is used to assess the relationship between exogenous and endogenous variables used in the research proposed model. A moderation effect is used to test whether COVID-19 or the company’s size is linked to the usage of DM and DT. The results are expected to reveal that DM and the digitalization process of enterprises affect brand promotion and brand position. The findings also imply that social media are widely used relative to other marketing channels. Companies that use DM and invest more in technology have better chances to promote and position their brands.